Use the quadratic formula to solve the equation. 2×2−6x+1=0 Enter your answers, in simplified radical form, in the boxes.

Question

Use the quadratic formula to solve the equation. 2×2−6x+1=0 Enter your answers, in simplified radical form, in the boxes.

in progress 0
Bella 2 weeks 2021-10-11T19:18:23+00:00 2 Answers 0

Answers ( )

    0
    2021-10-11T19:19:53+00:00

    X= -b +- square root of b^2-4ac
    ——————-
    2a

    6 +- square root of 36-4(2)(1)
    ———
    4

    6+- square root of 32
    ———
    4

    6+- 4 square root of 2
    ———
    4

    3 +- 2 square root of 2
    ———
    2

    0
    2021-10-11T19:20:00+00:00

    Answer with Step-by-step explanation:

    We have to solve the equation 2x²-6x+1=0

    the solution of the equation ax²+bx+c=0 is given by

    x=\dfrac{-b+\sqrt{b^2-4ac}}{2a}\ and\ x=\dfrac{-b-\sqrt{b^2-4ac}}{2a}

    Here a=2,b=-6 and c=1

    x=\dfrac{6+\sqrt{6^2-4\times 2\times 1}}{2}\ and\ x=\dfrac{6-\sqrt{6^2-4\times 2\times 1}}{2}\\\\x=\dfrac{6+\sqrt{36-8}}{2}\ and\ x=\dfrac{6-\sqrt{36-8}}{2}\\\\x=\dfrac{6+\sqrt{28}}{2}\ and\ x=\dfrac{6-\sqrt{28}}{2}\\\\x=\dfrac{6+2\sqrt{7}}{2}\ and\ x=\dfrac{6-2\sqrt{7}}{2}\\\\x=3+\sqrt{7}\ and\ x=3-\sqrt{7}

    Hence, solution of 2x²-6x+1=0 is:

    x=3+\sqrt{7}\ and\ x=3-\sqrt{7}

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )